PENGARUH DIVERSIFIKASI BISNIS TERHADAP KINERJA BISNIS TELKOM GROUP TAHUN 2018-2020 - Muhamad Ridho Chandra Sena; Wisnu Mawardi (Jurnal Akuntansi dan Pajak, 2023)
All companies are required to continue to grow by the company's stakeholders in order to be able to compete with its competitors. Product diversification is a strategy that can be used by companies to continue to grow by creating new business lines, either by creating similar products or products that are completely new and different from the previous company's main products. In addition, the benefit of product diversification is that the company does not depend on only one type of product and reduces the risk of the company's dependence so that when the company's main product enters the declining stage, the company still has other products that can be relied on for the sustainability of the company. The telecommunications industry is one of the most promising business areas, as seen from the technological developments that have continued to develop rapidly over the past few decades. The telecommunications network industry started from voice and visual services such as telephone and fax machines, to various kinds of digital content as it is today. PT Telkom Indonesia is one of the largest telecommunications companies in Indonesia and a State-Owned Enterprise (BUMN). The constantly changing industry conditions and intense market competition have not stopped the Telkom Group's business growth. Based on the Consolidated Financial Statements of PT Telekomunikasi Indonesia, throughout 2019 the Telkom Group was able to generate revenues of Rp 135.11 billion or an increase of 3.5% YoY compared to 2018. This study uses secondary data in the form of financial reports from each company included in the Telkom Group from 2018 to 2020. The sample selected in this study are 10 subsidiaries with consolidated direct ownership, namely Metranet, Telkomsel, Telkom Metra, Mitratel, PINs, Telkom Akses, Telin, Telkomsat, Telkom Infra, and Telkom Property. This study uses linear regression analysis techniques to test the hypotheses with the dependent variable, namely Return on Assets (ROA) as an indicator of business performance in the Telkom Group and several independent variables such as Leverage (LEV), Intangible Assets (INT_TA), Related Diversification (REL_DIV), and Unrelated Diversification (UNREL_DIV).